Learning Recovery after COVID-19 in Europe and Central Asia : Policy and Practice - Arcia, Gustavo; de Hoyos, Rafael; Patrinos, Harry; Sava, Alina; Shmis, Tigran; Teixeira, Janssen (World Bank, Washington, DC, 2021)
The vision of the Europe and Central Asia (ECA) Education Team is for education systems to empower all people to reach their full potential. In line with this vision, the purpose of this guidance note is to provide decision-makers with some recommendations and policy advice on effective ways to respond to the education losses engendered by the COVID-19 crisis. These recommendations include specific measures for mitigating learning losses and preparing for school reopening. The note also discusses the opportunity to design and implement structural reforms to make education systems more resilient and, in the process, improve students’ educational performance. Recommendations are also given for longer-term actions with the potential to transform education by strengthening learning and improving learning equity in the future.